Mosby's textbook for nursing assistants - Sorrentino, Sheila A.; Remmert, Leighann N. (Elsevier/Mosby, 2012)
With step-by-step instructions for over 100 nursing assistant procedures, Mosby's Textbook for Nursing Assistants, 8th Edition makes it easy to master the skills you need to succeed as a nursing assistant. Known for its visual approach and comprehensive, easy-to-read coverage, this market-leading text emphasizes the importance of the patient or resident as a person, communication, safety, comfort, effective delegation, and teamwork and time management. This edition provides expanded content on the person's rights and pressure ulcers. The updated companion CD includes three new procedures, an updated audio glossary, and more. Written by respected educator Sheila Sorrentino and expert co-author Leighann Remmert, Mosby's Textbook for Nursing Assistants makes nurse assisting easy to learn. Complete coverage includes the knowledge and skills needed by the nursing assistant; -- A clear, readable writing style is supplemented with hundreds of full-color photographs and illustrations; -- Over 100 procedures are divided into pre-procedure, procedure, and post-procedure sections for easier learning; -- Skills on the NNAAP exam are highlighted throughout and have been updated to match the 2012 test plan; -- Delegation Guidelines identify your specific responsibilities in accepting commonly delegated tasks; -- Teamwork and Time Management boxes indicate ways you can efficiently work with and help nursing team members; -- Promoting Safety and Comfort boxes detail measures and cautions for providing safe, effective patient care; -- Caring About Culture boxes help you learn about the beliefs and customs of other cultures so you can provide appropriate care; -- Focus on Children and Older Persons boxes provide age-specific information about the special needs, considerations, and circumstances of children and older persons; -- Focus on Long-Term Care and Home Care boxes highlight information vital to providing competent care in these settings; -- Focus on Communication boxes provide guidelines for what to say and ask when communicating with residents, visitors, and the nursing team; -- Key abbreviations are included at the beginning of each chapter, with a comprehensive glossary at the back of the book; -- Key terms introduce chapter content with the important words and phrases; -- Chapter Review Questions are useful in guiding your study, reviewing what you have learned, and studying for a test or the competency evaluation; -- CD icons indicate skills included on the companion CD; -- Video clip icons indicate skills for which video clips are included on the free Evolve companion website; -- Video icons indicate skills included in the Mosby's Nursing Assistant Video Skills 3.0 DVDs (sold separately); -- The Workbook and Competency Evaluation Review corresponds to chapters in the text and encourages learning with a wide variety of exercises and activities that challenge you to remember what you've learned. It also includes over 100 checklists, one for each procedure in the textbook. NEW! The Person's Rights and Pressure Ulcers chapters provides expanded information on these key areas; -- NEW Focus on PRIDE boxes highlight personal and professional responsibility, rights and respect, independence and social interaction, delegation and teamwork, and ethics and laws to help you promote pride in the person, family, and yourself; -- Two laminated, pocket-sized cards include information on normal vital signs, common measurement conversions, positioning, the 24-hour clock, and abdominal and lateral regions; -- Updated companion CD contains interactive procedures, including three new procedures, learning exercises, an updated audio glossary, and a new Spanish audio glossary with phrases and terms. An updated A&P review, Body Spectrum, is available on the CD and on the Evolve companion website.